Temporalne aspekty gier cyfrowych - Kochanowicz , Rafał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
Temporal issues related to digital games go beyond the strictly literary or film studies character of the description and implies technological and marketing issues. It can be outlined by referring to the concept of Andrzej Stoff, who analyzed the spatial dimension of the world of the novel (“delineating space”, “creating”, “functionalizing”, “valorising”). Relating these four detailed issues – constituting the basic subject of description, analysis and interpretation – to temporal aspects, it is appropriate to talk about measuring (conventionalizing, relativizing) time, thematizing, functionalizing and valorizing it. Taking into account the above categories, the most typical concretizations of temporal phenomena can be further defined: functional (classic chronometry, clock, server time, time of a running process), gameplay (real time, relativization, quest time, respawn time), thematic concretizations (e.g. retrospection as a compositional dominant of multimodal narratives) and marketing concretizations (commercialization of time).